Permeability Evolution and Particle Size Distribution of Saturated Crushed Sandstone under Compression - Yanlong Chen; Bangyong Yu; Kai Zhang; Mingwei Zhang; Guang Xu; Zhanqing Chen (Geofluids)
In this research, the particle size distribution and permeability of saturated crushed sandstone under variable axial stresses (0, 2, 4, 8, 12, and 16 MPa) were studied. X-ray Computed Tomography results revealed that particle crushing is likely to occur considerably as the axial stress is approaching 4 MPa, which results in the change of pore structure greatly. During compression, the particle size distribution satisfies the fractal condition well, and the fractal dimension of particle size distribution is an effective method for describing the particle crushing state of saturated crushed sandstone. When the axial stress increases from 0 MPa to 4 MPa, the fractal dimension of the particle size distribution increases rapidly by over 60% of the total increase (0–16 MPa), and the permeability decreases sharply by about 85% of the total decrease. These results indicate that 4 MPa is a key value in controlling the particle size distribution and the permeability of the saturated crushed sandstone under axial compression. The permeability is influenced by the initial gradation of the specimens, and a larger Talbot exponent corresponds to a larger permeability.